Advances in Research on the Bioactivity of Alginate Oligosaccharides - Xing, Maochen; Cao, Qi; Wang, Yu; Xiao, Han; Zhao, Jiarui; Zhang, Qing; Ji, Aiguo; Song, Shuliang (Marine drugs, 2020)
Alginate is a natural polysaccharide present in various marine brown seaweeds. Alginate oligosaccharide (AOS) is a degradation product of alginate, which has received increasing attention due to its low molecular weight and promising biological activity. The wide-ranging biological activity of AOS is closely related to the diversity of their structures. AOS with a specific structure and distinct applications can be obtained by different methods of alginate degradation. This review focuses on recent advances in the biological activity of alginate and its derivatives, including their anti-tumor, anti-oxidative, immunoregulatory, anti-inflammatory, neuroprotective, antibacterial, hypolipidemic, antihypertensive, and hypoglycemic properties, as well as the ability to suppress obesity and promote cell proliferation and regulate plant growth. We hope that this review will provide theoretical basis and inspiration for the high-value research developments and utilization of AOS-related products.